Daily evening melatonin prolongs survival among patients with advanced non-small-cell lung cancer. Issue 7 (3rd July 2022) - Hrushesky, William J. M.; Lis, Christopher G.; Levin, Robert D.; Grutsch, James F.; Birdsall, Timothy; Wood, Patricia A.; Huff, Dinah Faith Q.; Reynolds, Justin L.; Pearl, Dennis K.; Shen, Xiaotong; Gupta, Digant; Blask, David E.
ABSTRACT: Cancer patients show the signs and symptoms of a failing circadian organization. Melatonin, secreted only during nightly darkness, promotes nightly sleep and synchronizes daily molecular and physiologic clocks. Using a placebo-controlled randomized double-blind clinical trial, we determined whether the hypothesized proper physiologic daily timing, the evening, is essential for cancer patients to benefit from melatonin. Eighty-four advanced non-small cell lung cancer (NSCLC) patients from two centers (42 each) receiving standard etoposide/cisplatin therapy, were randomly assigned to one of three arms (I, 8AM & 8PM placebo; II, 8AM 20 mg melatonin and 8PM placebo; III, 8AM placebo and 8PM 20 mg melatonin. Each patient was followed until death. After adjusting for covariates, the Cox proportional hazards regression analysis found that the overall survival was enhanced only among those patients randomized to receive evening melatonin ( p = 0.031 HR = 0.39). Survival benefit in the PM melatonin arm was optimized in patients who reported normal sleep quality. After adjusting for significant covariates at baseline, we found an overall survival advantage for PM melatonin when compared against placebo. Moreover, PM melatonin's therapeutic effect was optimal in patients who self-reported normal sleep quality.